2023
DOI: 10.1038/s41420-023-01372-7
|View full text |Cite
|
Sign up to set email alerts
|

MiR-130a-3p regulates FUNDC1-mediated mitophagy by targeting GJA1 in myocardial ischemia/reperfusion injury

Abstract: Understanding the complex pathogenesis in myocardial ischemia/reperfusion (I/R) injury (IRI) is an urgent problem in clinical trials. Increasing pieces of evidence have suggested that miRNAs are involved in the occurrence and development of heart diseases by regulating mitochondria-related gene expression. Mitochondria have been acknowledged as the key triggers of cardiac I/R injury. However, the potential impact of miR-130a on mitochondria remains unclear in myocardial IRI. Exploring the regulatory mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Various miRNAs, such as remodelling, hypertrophy, apoptosis, and hypoxia, play a role in the pathogenic mechanism leading to HF 24 . For example, miR‐130a‐3p regulates FUNDC1‐mediated mitophagy by targeting GJA1 in myocardial ischaemia/reperfusion injury 25 . In addition, miRNAs respond to the progression of HF in a dynamic and stage‐specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Various miRNAs, such as remodelling, hypertrophy, apoptosis, and hypoxia, play a role in the pathogenic mechanism leading to HF 24 . For example, miR‐130a‐3p regulates FUNDC1‐mediated mitophagy by targeting GJA1 in myocardial ischaemia/reperfusion injury 25 . In addition, miRNAs respond to the progression of HF in a dynamic and stage‐specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins include FUNDC1, BNIP3, and NIX. FUNDC1 is an important receptor protein located in the outer mitochondrial membrane, and when mitochondria are damaged, the LIR motif in FUNDC1 activates mitophagy by molecularly docking with LC3 protein through hydrophobic interaction [19]. BNIP3 is located in the outer mitochondrial membrane and contains a transmembrane domain with the C-terminus inserted into the outer mitochondrial membrane and the N-terminal storm in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…IRI causes organ damage and delays return of graft function after transplantation (Yang & Klionsky, 2010). Counteracting cell death by removing damaged macromolecules or organelles makes autophagy an essential focus of IR treatment and prevention strategies during transplantation (Mao et al, 2023). Studies have indicated that autophagy and its regulation are potential therapeutic targets in IRI and offer hope for reducing IRI by enhancing the protective mechanism.…”
Section: Autophagy In Transplantationmentioning
confidence: 99%
“…Although autophagy can promote cell survival by recycling components, excessive autophagy can lead to cell death. Because of this dual pathway, modulation of autophagy may be the key to treating IRI (Mao et al, 2023). Lipid droplets (LDs) are neutral lipid storage organelles that play a crucial role in lipid homeostasis.…”
mentioning
confidence: 99%